2011
DOI: 10.1049/el.2011.1695
|View full text |Cite
|
Sign up to set email alerts
|

Large-area solar-blind AlGaN-based MSM photodetectors with ultra-low dark current

Abstract: Large-area metal -semiconductor -metal (MSM) solar-blind photodetectors with a device area of 5 × 5 mm 2 have been fabricated on Al 0.4 Ga 0.6 N/AlN/sapphire epistructure. The photodetector exhibits ultra-low dark current density of 3.2 × 10 212 A/cm 2 under 20 V bias and a corresponding breakdown voltage of up to 385 V. The solar-blind/ultraviolet rejection ratio of the photodetector is more than four orders of magnitude with a maximum quantum efficiency of 28% at 275 nm.Introduction: Wide bandgap AlGaN-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…In general, the Al x Ga 1− x N layers for MSM device application grow on sapphire substrates via MOCVD, MBE, sputtering method, and metal–organic vapor phase epitaxy (MOVPE) . In order to push forward with the growth of high‐quality Al x Ga 1− x N layers and also to promote the adhesion between the layers and substrates, GaN or AlN layers with thickness of tens to hundreds of nanometers were often employed as buffer or nucleation layers . It has been found that with the increase of x value, the peak response as well as the cutoff wavelengths of the MSM photodetectors manifested obvious blue transfer to shorter wavelength, an indicative of variation in the Al x Ga 1− x N bandgap.…”
Section: Iii‐nitride Compoundsmentioning
confidence: 99%
“…In general, the Al x Ga 1− x N layers for MSM device application grow on sapphire substrates via MOCVD, MBE, sputtering method, and metal–organic vapor phase epitaxy (MOVPE) . In order to push forward with the growth of high‐quality Al x Ga 1− x N layers and also to promote the adhesion between the layers and substrates, GaN or AlN layers with thickness of tens to hundreds of nanometers were often employed as buffer or nucleation layers . It has been found that with the increase of x value, the peak response as well as the cutoff wavelengths of the MSM photodetectors manifested obvious blue transfer to shorter wavelength, an indicative of variation in the Al x Ga 1− x N bandgap.…”
Section: Iii‐nitride Compoundsmentioning
confidence: 99%
“…prepared a large‐area AlGaN MSM‐PD of 5 × 5 mm 2 with the structure of Al 2 O 3 /AlN/Al 0.4 Ga 0.6 N/Ni/Au, which exhibited an ultralow dark current density of 3.2 × 10 −12 A cm −2 at 20 V bias, a UV–visible suppression ratio up to 10 4 , and a very high breakdown voltage. [ 89 ]…”
Section: Research Status Of Msm‐pdsmentioning
confidence: 99%
“…Commonly, the AlGaN detector structures are realized on sapphire substrates. The large lattice mismatch between the absorber layer and the substrate results in a high threading dislocation density (TDD) in the absorber, which enhances carrier recombination and reduces the detector responsivity . Several approaches to reduce the TDD, e.g., selective area epitaxy, growth on patterned sapphire substrates (PSS), and mask‐less epitaxial lateral overgrowth (ELO) have been reported.…”
Section: Introductionmentioning
confidence: 99%